Dimensões institucionais associadas à abertura de dados governamentais: uma análise transnacional - Santos, Jaedson Gomes dos (2020)
In order to meet global demands for greater transparency, citizen participation and collaboration, the Open Government Partnership (OGP) was formed in 2011. Following this and other events, governments around the world have, gradually, adopted a new standard required for the disclosure of data generated by the public sector. This new standard is known as Open Government Data (OGD) and determines the availability of data without legal or technical restrictions, enabling the information to be reused with the purpose of creating new products and services. With the gradual adoption of the OGD in the national public administrations, the Academy has mobilized to investigate which are the benefits and barriers in the process for opening government data. However, despite considerable contributions in the literature, it’s possible to affirm that there is a lack of analyses that take in consideration the influence of institutional factors on the OGD. Given this scenario, the goal of this study is to investigate the relationship between the institutional dimensions and the levels of government data openness in different countries. To reach that goal, the research follows a quantitative approach, from the standpoint of a cross-sectional study design research. In regards to the operationalization of the variables, we have used secondary data referring to 2016 and made available in sources such as the Web Foundation, the UN statistical division, the OGP and the V-Dem Institute. Furthermore, the analysis took place in two stages, a descriptive analysis and a multivariate analysis, with the application of a multiple linear regression model. The results found that, up to the date of this analysis, most countries were in the initial stages of their OGD initiatives and that institutional dimensions such as the degree of existence of a OGD-specific policy, the development of e- government programs, the participation of the country in the OGP and the administrative quality of government are factors directly related to the level of data openness in each country. With these results, therefore, it’s possible to conclude that institutional dimensions matter when it comes to explaining the performance of governments to opening their data, and that together with the technical and management challenges, the OGD initiatives also imply great institutional challenges for national public organizations.